2018
DOI: 10.15366/rimcafd2018.72.006
|View full text |Cite
|
Sign up to set email alerts
|

Relación Entre Composición Corporal Y Movimientos Realizados Durante La Marcha en Mujeres

Abstract: Rev.int.med.cienc.act.fís.deporte -vol. 18 -número 72 -ISSN: 1577-0354 693 Leirós-Rodríguez, R.; Romo-Pérez, V.; Arce-Fariña, M.E. y García-Soidán, J.L. (2018) Relación entre composición corporal y movimientos realizados durante la marcha en mujeres / Associations Between Body Composition and Movements During Gait in Women. Revista Internacional de Medicina y Ciencias de la Actividad Física y el Deporte vol. 18 (72) pp. 693-707 ABSTRACTThe aim of this paper is to explore the relationships between gait paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…In the children included in this study, no relationship was observed between body weight or BMI and the result of any of the clinical indicators or accelerometric variables, which is in contrast to the results obtained in previous studies conducted with adolescents and pre-adolescents [25,26]. It has been demonstrated that obesity modifies the geometry of the body, increasing the weight and volume of the limbs and, consequently, the predisposition to falling, due to biomechanical limitations [26,27]. Therefore, this controversial finding may be due to the young age of the study sample, or the lack of overweight and obese participants who could confirm the existence of such a relationship between BMI and postural control during childhood.…”
Section: Discussioncontrasting
confidence: 89%
“…In the children included in this study, no relationship was observed between body weight or BMI and the result of any of the clinical indicators or accelerometric variables, which is in contrast to the results obtained in previous studies conducted with adolescents and pre-adolescents [25,26]. It has been demonstrated that obesity modifies the geometry of the body, increasing the weight and volume of the limbs and, consequently, the predisposition to falling, due to biomechanical limitations [26,27]. Therefore, this controversial finding may be due to the young age of the study sample, or the lack of overweight and obese participants who could confirm the existence of such a relationship between BMI and postural control during childhood.…”
Section: Discussioncontrasting
confidence: 89%
“…The following inclusion criteria were used: (a) engaged in physical activity between 1 and 2 days/week; (b) walked between 30 and 90 min 4 days a week; (c) be over 50 years; and (d) have a good level on independence and gait stability (could complete the Timed Up and Go Test in 10 s or less) [23].…”
Section: Samplementioning
confidence: 99%
“…At the same time, they also indicate the need to identify a set of accelerometric variables in order to define a solid, objective and reliable model for the clinical assessment of equilibrium [19][20][21]. In this line, the studies of Leirós-Rodríguez et al [22,23] have advanced, in which the reliability of the records from the fourth lumbar vertebra was confirmed, the suitability of the realisation of the static equilibrium tests for 30 s was assessed and the creation of a tool composed of three static equilibrium tests was reported [24]: two tests on the ground in monopodal support (one with open eyes and one with closed eyes) and a test on a mat with monopodal support with open eyes. From the accelerometric records during the same period, eleven variables should be drawn, all of which refer to the maximum and/or averaged values obtained in the vector module, in the sagittal plane (for the test of monopodal equilibrium on mat) and the frontal plane (for the tests of monopodal balance on the ground).…”
Section: Introductionmentioning
confidence: 99%